2008
DOI: 10.3354/dao01906
|View full text |Cite
|
Sign up to set email alerts
|

Variable region of betanodavirus RNA2 is sufficient to determine host specificity

Abstract: Betanodaviruses, the causative agents of viral nervous necrosis in marine fish, have bipartite positive-sense RNA genomes. The viruses have been classified into 4 distinct types based on nucleotide sequence similarities in the variable region (the so-called T4 region) of the smaller genomic segment RNA2 (1.4 kb). Betanodaviruses have marked host specificity, although the primary structures of the viral RNAs and encoded proteins are similar among the viruses. We have previously demonstrated, using reassortants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 25 publications
(38 reference statements)
2
53
0
Order By: Relevance
“…The existence of these two changes was also observed in the 16 reassortant isolates that were partially sequenced. These results confirmed that C-terminal protruding domains of the capsid protein are involved in host specificity, as reported previously (Iwamoto et al, 2004;Ito et al, 2008). However, the other change was observed in the N-terminal one-third of the protein.…”
Section: J G Olveira and Otherssupporting
confidence: 80%
See 1 more Smart Citation
“…The existence of these two changes was also observed in the 16 reassortant isolates that were partially sequenced. These results confirmed that C-terminal protruding domains of the capsid protein are involved in host specificity, as reported previously (Iwamoto et al, 2004;Ito et al, 2008). However, the other change was observed in the N-terminal one-third of the protein.…”
Section: J G Olveira and Otherssupporting
confidence: 80%
“…All of the reassortant strains exhibited a slightly modified SJNNV capsid, with three different amino acid positions in all strains (the differences increased to a maximum of six in some strains). One of these changes observed in residue 247 was encoded by the nucleotide triplet 737-739, included in the sequence nt 695-765, described by Ito et al (2008) as a hostspecific determinant. Another change in the amino acid sequence (aa 270) was also observed on the C-terminal side of the capsid protein.…”
Section: J G Olveira and Othersmentioning
confidence: 99%
“…Considering that even striped jack has a strict age-dependent resistance against SJNNV (Arimoto et al, 1993), less susceptible Japanese jack mackerel might be more resistant at juvenile or older stages and thus possibly develop into subclinical infection. We previously reported that RNA2 determines the host-specificity of betanodaviruses (SJNNV and RGNNV) and the T4 region in RNA2 is particularly important for pathogenicity (Iwamoto et al, 2004;Ito et al, 2008). After the first report on SJNNV of striped jack larvae in 1992 (Mori et al, 1992), the SJNNV genotype was detected by cell culture isolation or PCR from cultured Senegalese sole Solea senegalensis, sea bass Dicentrarchus labrax, and gilthead sea bream Sparus aurata in southern Europe, and these European SJNNVs are phylogenetically different from Japanese SJNNVs all of which were isolated from diseased striped jack larvae (Thiéry et al, 2004;Cutrín et al, 2007;Toffolo et al, 2007;Olveira et al, 2009;Cherif et al, 2011;Panzarin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It showed that VNN has the ability to infect across species and adapt to a new host species [19]. A specific host on the most viral infections are usually controlled by the interaction with a viral surface protein receptors on the surface of target cells precisely [31], so long as the tilapia have receptors that can bind to the attachment site (s) virus particles, then certainly virus will entry into host cells (tilapia), because it does not directly host cell have facilitated the virus to enter the cell [32]. The tilapia have such receptors HSC70, as well as groupers [33], which specifically alleged that the virus can perform attachment and involved in an interaction that could cause the virus to enter the body tilapia.…”
Section: Rt-pcr and Sequencingmentioning
confidence: 99%